(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article investigates the linguistics of virtual reality and the speech dynamics of emotions and abbreviations in the language of social networks. The results of the analysis illuminate the close interdependence between linguistic change and social relations, as well as the systematic impact that digital platforms exert on the culture of communication.